Aplicação do extrato hidroalcóolico das folhas de Syzygium malaccense e estudos da estabilidade e atividade antioxidante em bases aniônica e não iônica - Zanchet, Eloisa Regina (2021)
Syzygium malaccense, popularly known as Jambo, is a native plant of Malaysia, belonging to the Myrtaceae family, in Brazil it is found in the North and Northeast regions. Some studies show that jambo has compounds rich in antioxidant and anti-inflammatory activity. In this context, the objective of this work was to incorporate the extract of jambo leaves in cosmetics and to evaluate the stability and antioxidant potential of the creams. The extract of the jambo leaves was produced by heating the dried and crushed jambo leaves with an extracting mixture of ethanol:water (40:60v/v). Subsequently, the extract was lyophilized and analyzed for antioxidant power using in vitro techniques, DPPH, ABTS radical scavenging, iron ion reduction method (FRAP), by the content of total phenolic compounds and identification of individual phenolic compounds by high performance liquid chromatography (HPLC). The extract obtained showed high antioxidant power and the compounds gallic acid and myricitrine, were identified. The extract was incorporate ed at a concentration of 1.5% in the anionic and non-ionic base formulations. And the formulations were evaluated for preliminary stability during heat stress (0 to 12 days), through organoleptic characteristics, pH, spreadability, homogeneity and DPPH antioxidant activity. The formulations proved to be stable during the preliminary study and were approved for the accelerated study, where they were evaluated for 90 days under ambient, oven and refrigerator temperature conditions. At times 30, 60 and 90 days, analyzes of pH, spreadability and antioxidant activity were performed using the DPPH• method, and at the end of the study, colorimetric analysis was performed to assess the color of each cream in its environment. The antioxidant activity was expressed as EC50, that is, the concentration necessary to inhibit 50% of the DPPH• radical. The formulations showed little variation in pH according to the time and environment analyzed. The samples analyzed at refrigerator temperature were the ones with the greatest luminosity (L*), followed by room and oven temperature. The antioxidant activity (EC50), analyzed on the first day after preparing the creams with the addition of extract, was 1.90 and 2.69 mg mL-1, for the anionic and non-ionic, respectively, while the bases without addition of extract showed no activity. The antioxidant activity in 90 days of analysis for the anionic cream was 2.09 mg mL-1, for the samples stored in the refrigerator, 2.36 mg mL-1, for room temperature and 2.71 mg mL-1, for greenhouse. The EC50 for the nonionic cream in 90 days was 4.94 mg mL-1 in the refrigerator, 5.15 mg mL-1 at room temperature and 5.26 mg mL-1 in the oven. The extract provided antioxidant activity in both formulations, but had better interaction with the anionic formulation, demonstrating the best antioxidant potential.